Stable transmission of solitons on WDM communication system - Shum, Ping. (2008)
A prominent advantage of solitons is that they have stable propagation characteristics and are very robust to perturbations during transmission. As the first step to a successful soliton-based communication system, an ultrahigh-speed soliton light source is indispensable not only for the development of ultrahigh-speed optical time- division multiplexing (OTDM) but also for the future ultrahigh-speed dense wavelength- division multiplexing (DWDM) communications. Thus, this report will address such important issues: how to provide an optical source that can produce stable and high repetition rate soliton pulse trains with ultrashort pulse duration. The research will attempt to develop such an optical source from an erbium-doped fibre ring laser. The aims of this report are to construct a stable soliton laser source by a novel configuration, and to characterize and optimize the performance of this laser. This laser source will be a useful light source for high-speed optical communications, such OTDM, high speed WDM or a combination of OTDM and WDM